(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
Pulmonary embolism (PE) is a major cause for morbidity and mortality. Following trauma to lower extremities, thrombus formation is a well-know entity, and one needs to foresee the possibility of embolism and eventual death. It is imperative and the onus solely rests on the treating doctor to weigh the risk factors for thrombus formation like age, sex, obesity, fracture, and immobilization and take necessary precautions to prevent pulmonary embolization. Two such cases with fractures of lower limb bones, where the deceased were middle aged, obese and immobilized for a period of time, died following muscular activity and autopsy revealed PE.